The impact of IEQ on occupants’ satisfaction in Malaysian buildings - Kamaruzzaman, Syahrul Nizam; Egbu, Charles O.; Mahyuddin, Norhayati; Ahmad Zawawi, Emma Marinie; Chua, Shirley Jin Lin; Azmi, Nur Farhana (SAGE Publications, 2018)
This paper focuses on the importance of occupant satisfaction with indoor environmental quality in buildings as well as the effect of indoor environmental quality towards occupants’ satisfaction. This research applied post-occupancy evaluation as a method to indicate the building occupants’ needs, their satisfaction and comfort level. The research is based on a case study approach whereby a questionnaire survey was conducted among 25 organizations involved in managing office buildings. A total of 115 questionnaires were returned for evaluation of occupants’ overall satisfaction from aspects of indoor environmental quality in these buildings and to determine the occupants’ satisfaction level within these buildings. The findings revealed that indoor environment factors that could contribute to occupants’ satisfaction consists of lighting, air quality and aesthetic perception. These classifications were made based on the factor analysis done with 22 attributes of the indoor environment. The majority of occupants are satisfied with their health conditions and do not face any serious health problems. However, occupants highlighted that some environmental conditions, health effects, air movement, ventilation and air freshness are important criteria for their satisfaction and comfort. This study provides insights into how occupants perceive their indoor environment and comfort, and identify problems that could arise in buildings.